2012
DOI: 10.1155/2012/696704
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Oxidative and Nitrosative Apoptotic Signaling by L-Carnitine in Ifosfamide-Induced Fanconi Syndrome Rat Model

Abstract: It is well documented that ifosfamide (IFO) therapy is associated with sever nephropathy in the form of Fanconi syndrome. Although oxidative stress has been reported as a major player in IFO-induced Fanconi syndrome, no mechanism for this effect has been ascertained. Therefore, this study has been initiated to investigate, on gene expression level, the mechanism of IFO-induce nephrotoxicity and those whereby carnitine supplementation attenuates this serious side effect of IFO. To achieve the ultimate goals of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 54 publications
1
9
0
Order By: Relevance
“…In pathological states of the renal system, it may go to the extreme irreversible dedifferentiation states.Urine lactate has been shown to be increased in Fanconi's syndrome (168). Increased NO due to iNOS activation has been shown in animal model Fanconi's syndrome (169). It has been already shown that in response to injury to renal system, the surviving cells dedifferentiate and repair the injury (161).…”
Section: Renal Dysfunction In Sepsis Aki Ckd Pkd and Fanconi's Synmentioning
confidence: 99%
“…In pathological states of the renal system, it may go to the extreme irreversible dedifferentiation states.Urine lactate has been shown to be increased in Fanconi's syndrome (168). Increased NO due to iNOS activation has been shown in animal model Fanconi's syndrome (169). It has been already shown that in response to injury to renal system, the surviving cells dedifferentiate and repair the injury (161).…”
Section: Renal Dysfunction In Sepsis Aki Ckd Pkd and Fanconi's Synmentioning
confidence: 99%
“…Other mechanisms by IPM that reduce cancer proliferation, including activation of proapoptotic pathways and reduction of inflammatory and antiapoptotic pathways, have also been suggested [12, 13] (Fig. 2).…”
Section: Pharmacodynamicsmentioning
confidence: 99%
“…Both CYP3A and CYP2B6 catalyze this reaction, but striking differences are observed: CYP3A4/5 preferentially produced (R)- N -2-DCl-IFO and (R)- N -3-DCl-IFO from R-IFO and S-IFO, respectively, whereas CYP2B6 preferentially formed (S)- N -3-DCl-IFO and (S)- N -2-DCl-IFO. On the basis of these in-vitro data, R-IFO exhibits more rapid 4-hydroxylation and less efficient N -dechloroethylation to toxic metabolites than S-IFO, suggesting that R-IFO may have a distinct clinical advantage over racemic IFO [12]. Although in-vivo studies on the metabolism and disposition of the R-enantiomer and S-enantiomer of IFO have not been fully evaluated, the limited clinical data available are consistent with the in-vitro evidence.…”
Section: Pharmacokineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…Carnitine binds to the chloroacetyl-CoA, detoxifies it, and the chloro-acteyl-carnitine is excreted in the urine. This detoxification results in a secondary deficiency of carnitine in patients receiving ifosfamide (Peluso et al, 2000;Sayed-Ahmed et al, 2012). Cisplatin can damage the kidney resulting in a reduction in glomerular filtration and tubular damage.…”
Section: Introductionmentioning
confidence: 99%